Human Development in Uganda : Meeting Challenges and Finding Solutions - World Bank (Washington, DC, 2013)
The Millennium Development Goals (MDGs) set ambitious targets for economic and social development, earmarking eight broad targets. Uganda appears to be on track to meet four of these goals by 2015: halving the poverty rate, eliminating gender disparities in primary school, halving the number of people without safe drinking water, and reversing the spread of AIDS. The country s performance is off track, however, in achieving substantial reduction in infant, child and maternal mortality, halving the number of people without access to sanitation facilities, eliminating gender disparities in secondary school, and achieving 100 percent primary school enrolment. This report seeks to identify challenges to improvement of human development outcomes, and to suggest ways of dealing with these challenges in order to improve service delivery, and therefore progress in human development indicators. It examines how well Uganda has moved toward achieving its PEAP targets for human development, focusing on three sectors: education, health care, and water and sanitation. The report argues that the key to improvement in social services - whether it be education, health care, or water and sanitation - is a new more efficient service delivery framework, a framework with improved links among the policymakers who shape broad goals, the providers of the services, and the customers who are the recipients.